Pathogenicity of RNA satellite associated with cucumber mosaic virus (CMV) on chilli (Capsicum annuuum L.) - Mai Sari; Mahfut; Sijabat, Veronica Elizabeth (Genetikawan Muda Indonesia, 2023)
Obstacles that often occur in cultivation of tomatoes, chilies, and tobacco is the occurrence of diseases caused by viruses. One of them is infected with the Cucumber mosaic virus (CMV), this virus infection is very dangerous for large red chili, tomato and tobacco farming which results in quite large losses for farmers in Indonesia. Controlling viral infections caused by CMV is very difficult due to the high genetic diversity of CMV making it difficult to obtain resistant types of red pepper, tomato and tobacco, the range of CMV host plants is wide, and CMV can be transmitted by aphids and ticks. non-persistent whiteheads. The aim of this journal review was to determine the pathogenicity of sat-RNA associated with CMV in red chilies, tomatoes and tobacco. Based on the results of reviews from several journals, it can be seen that RNA satellite is effective against CMV infection on chili, tomato, and tobacco plants. Which can be seen by administering the CARNA vaccine to each plant treatment.